2007
DOI: 10.1080/09603100600694327
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic interactions between private investment and the stock market: evidence from cointegration and error correction models

Abstract: This study examines the dynamic interdependencies between private investment and the stock market for the US economy for the 1970 to 2003 period. The main findings are as follows. First, both investment and stock prices seem to adjust to disequilibria from each other in the long run. Second, past changes in nominal investment have a positive effect on stock prices in the short-run but changes in real investment do not. Third, changes in real stock prices do not affect real investment but past changes in nomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…The Phillips-Perron as cited in Laopodis and Sawhney [35] unit root test is very general and can be used in the presence of heteroscedastic and autocorrelated innovations is specified as follows Eq. 2:…”
Section: Unit Root Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Phillips-Perron as cited in Laopodis and Sawhney [35] unit root test is very general and can be used in the presence of heteroscedastic and autocorrelated innovations is specified as follows Eq. 2:…”
Section: Unit Root Testsmentioning
confidence: 99%
“…The third hypothesis is that the series contains a unit root but without a drift or a time trend: 3 0 H : a = 0, β = 0, δ = 1. The statistics that are used to test each hypothesis are Z(t δ ), Z(Φ 2 ), Z(Φ 3 ), respectively and their corresponding equations are as follows as cited in Laopodis and Sawhney [35] Eq. 2a-e:…”
Section: Equation 2 Tests Three Hypothesesmentioning
confidence: 99%
“…The dynamic specification of the model allows the deletion of the insignificant variables, while the error correction term is retained by the estimation of the co-integrated vector. : 1975: -2007 A short-run increase of economic growth per 1% induces an increase of bank credits per 0.006%, while an increase of consumer price index per 1% induces a decrease of bank credits per 1.05 for United Kingdom Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Following the studies of Vazakidis and Adamopoulos (2009c;, the Phillips-Perron unit root test according to Laopodis and Sawhney (2007), is very general and can be used in the presence of heteroscedastic and autocorrelated innovations is specified as follows Eq. 2a:…”
Section: Unit Root Testsmentioning
confidence: 99%
“…For instance, according to AlKhazali et al (2006), the market liberalization and the attempts by the governments in this region to integrate the financial markets could be one reason that there may be some level of integration in the subset of the equity markets of the GCC countries. Another study by Laopodis and Sawhney (2007) showed that there is a dynamic interaction between private investment and the equity markets for the US economy. In yet another study by Abumustafa (2008), it was noted that there are a number of political and ideological differences between the different economies in Middle Eastern markets.…”
Section: Introductionmentioning
confidence: 98%